2020
DOI: 10.1096/fj.202001604r
|View full text |Cite
|
Sign up to set email alerts
|

Activin A increases human trophoblast invasion by upregulating integrin β1 through ALK4

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…After being affected by mechanical forces, integrin binds to its ligands and mediates FAK, PI3K, AKT/PKB, and other signaling pathways that regulate cell proliferation, migration, and epithelial-mesenchymal transition [ 67 , 68 ]. By upregulating integrin-β1, the invasion of human trophoblasts can be promoted [ 69 ]. We also examined the expression of integrin-β1 of JAR cells on different regions and found no significant differences either between soft and inter or between inter and stiff, with stiff being slightly higher than soft ( Figure S4 ), and the expression of other subunits of integrin did not change significantly with substrate stiffness [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…After being affected by mechanical forces, integrin binds to its ligands and mediates FAK, PI3K, AKT/PKB, and other signaling pathways that regulate cell proliferation, migration, and epithelial-mesenchymal transition [ 67 , 68 ]. By upregulating integrin-β1, the invasion of human trophoblasts can be promoted [ 69 ]. We also examined the expression of integrin-β1 of JAR cells on different regions and found no significant differences either between soft and inter or between inter and stiff, with stiff being slightly higher than soft ( Figure S4 ), and the expression of other subunits of integrin did not change significantly with substrate stiffness [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activin A plays important roles in regulating the biological behavior of trophoblasts. Previous studies have shown that activin A promotes human trophoblast invasion, as evidenced by a Transwell invasion assay in HTR8/SVneo cells [ 20 , 31 , 60 ]. The vascular channels of human utero-placental bed are lined by trophoblasts, which acquire the functional characteristics of vascular endothelial cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, among all human tissues and single cell types, fibronectin is most abundant in human placental tissue and extravillous trophoblasts [ 29 , 30 ]. According to the research of Zhu et al [ 31 ], transcriptome profiles of HTR8/SVneo trophoblast cells with and without activin A treatment show the most significant changes in the ECM interaction pathway. Moreover, in normal pregnancies, maternal circulating concentrations of both fibronectin [ 32 , 33 ] and activin A [ 34 , 35 ] tend to increase progressively throughout pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this process contributes to the induction of ECM stiffness, which has been associated with the pathogenesis of hypertension [86]. Apart from these findings, research has revealed that pregnancy-induced hypertension represents a notable form of hypertension attributable to a deficiency in activin A [127]. This deficiency exerts its influence by suppressing the ActRII/ALK4/SMAD2/3/4 signaling pathway, subsequently upregulating β1 integrin expression on trophoblasts [127].…”
Section: Pdgf-bbmentioning
confidence: 99%